Mixed-mode fracture toughness of texturized LS2 glass-ceramics using the three-point bending with eccentric notch test - Belli, Renan; Wendler, Michael; Petschelt, Anselm; Lohbauer, Ulrich (Dental Materials, 2017)
Here we use the 3-point bending with eccentric notch test (3-PBEN) to investigate the fracture behavior of a pressable and a CAD/CAM lithium disilicate (LS2) glass-ceramics under combined mode-I and mode-II loading. The effect of the bulk texturization in the beams of the pressable LS2 is made visible through the fracture trajectory following the most energetically favorable path dictated by the crystallite alignment. The CAD/CAM LS2 shows an isotropic fracture mode but increasing fracture energy with mode-II contribution, similar to the pressable variant.
EVALuna2:24691